Aktivitas Keluar Sarang Heterotrigona itama Cockerell. (Hymenoptera: Apidae: Meliponinae) di Taman Hutan Raya Pocut Merah Intan, Kabupaten Aceh Besar, Aceh, Indonesia - Suwarno, Suwarno; Akbar, Novrizal; Rizki, Alia; Siregar, Zuriana (BIOEDUSCIENCE, 2023)
Background: The study conducted in the Pocut Meurah Intan Forest Park (TAHURA PMI) area aimed to analyze the outgoing activity of Heterotrigona itama worker beehives and their relationship with environmental and physical factors such as temperature, humidity, and light intensity. Methods: H. itama activity is observed from 06.00 to 18.00 WIB. Bees exiting the hive are counted using manual counting to determine the number of individuals that exit the hive for 10 minutes every hour. Observation of activities outside the nest consists of foraging, throwing garbage, and drones guarding the nest. Results showed that the peak of activity out of H. itama nests occurred at 09.00 - 10.00 WIB and 13.30 - 14.30 WIB. Results: Foraging activity was the highest nest exit activity. The relationship between light intensity factor and activity outside the foraging nest is moderate (R2 = 0.651), while temperature and humidity are weak (R2 = 0.052 and 0.091). The activity of exiting the nest to throw garbage has a moderate relationship with light intensity (R2 = 0.439) compared to temperature (R2 = 0.253) and humidity (R2 = 0.296). Furthermore, physical factors of light intensity (R2 = 0.6217) had a greater relationship with drone activity out of the nest than factors of temperature (R2 = 0.4385) and humidity (R2 = 0.4063). Activity outside the nest is positively correlated with temperature and light intensity and negatively correlated with humidity. Conclusions: Thus, it can be concluded that light intensity has the greatest influence on the activity out of the nest.